Offender patients’ opinions on placement in a forensic hospital - Margetić, Branimir; Ivanec, Dragutin; Žarković Palijan, Tija; Kovačević, Dražen (2012)
Background People who become patients in secure hospitals may not understand their situation and have different opinions about the nature of institutionalisation from each other and from staff and the authorities. More knowledge of patient perspectives could improve treatment outcomes. Aims Our aim was to evaluate patients’ beliefs about whether placement in an institution should be mainly punitive, therapeutic or a mixture of both and whether offence type should have any influence on the nature of the institutionalisation. Methods Inpatients with schizophrenia or schizoaffective disorder, from the Department of Forensic Psychiatry in Popovaca, Croatia, were asked to report their personal opinions about appropriateness of placements according to three case vignettes related to psychotically motivated offences of (1) homicide ; (2) property damage ; and (3) arson. Results A total of 52 patients were eligible for participation and consenting. Their average age was 44 (9.56) years and the mean duration of treatment in the specialist hospital was 7.7 (5.59) years ; just over a third of them (20 patients) had committed or attempted homicide. They were more likely than not to favour at least 5 years of detention in a secure hospital for a person with psychosis who had killed another, regardless of mental state, but that for minor property damage, improvement in mental state should be the key determinant of discharge. They were more equivocal about arsonists. Conclusions Perceptions of male offenders with psychosis on determinants of length of stay in a secure hospital appear to have much in common with what one would expect in the wider community. The fact that in spite of generally having poor insight into their own situation, these men could make judgments about fictitious but similar patients that appeared so unremarkable raised the possibility of building on this vignette study towards an educationally therapeutic module in preparation for rehabilitation.
ENG